TARGETED DRUG DELIVERY THROUGH CRISPR‒CAS9: BRIDGING BIOPHARMACEUTICS AND PHARMACOKINETICS - RAMASAMY, JUBILEE; JAISANKAR, DHARSHINI; RAMAMOORTHY, SURUTHI; JOTHIBASU, DEEPIKA; RAVIKUMAR, NIRANJANI (International Journal of Applied Pharmaceutics, 2025)
Precision medicine transforms healthcare by tailoring treatment methods to individual patient characteristics. Clustered Regularly Interspaced Short Palindromic Repeats associated protein 9 (CRISPR-Cas9) gene editing serves as the primary technological force enabling effective targeted alterations of specific genetic information. This analysis provides a clear overview of how CRISPR-Cas9 technologies enhance drug distribution systems and pharmacologic process management. The combination of CRISPR‒Cas9 technology with gene therapy and targeted drug delivery systems leads to improvements in therapeutic effectiveness. CRISPR‒Cas9 technology delivers three distinct functional abilities to the medical field including drug target detection along with enhanced targeted delivery mechanisms and gene-edited pharmacokinetic management. The CRISPR‒Cas9 system creates advancements in precision medicine development. The analysis explores new drug delivery techniques alongside CRISPR‒Cas9 role in medication transport systems and biochemical processing mechanisms. Modern drug delivery systems developed from CRISPR‒Cas9 technology and biopharmaceuticals will build the next generation of precision medicines. Through its ability to regulate drug activation and bioavailability the CRISPR‒Cas9 system plans to revolutionize future medicine supply networks.